Comparative evaluation of cone-beam computed tomography versus direct surgical measurements in the diagnosis of mandibular molar furcation involvement - Shyam Padmanabhan; Ahila Dommy; Sanjeela R Guru; Ajesh Joseph (Contemporary Clinical Dentistry, 2017)
Aim: Periodontists frequently experience inconvenience in accurate assessment and treatment of furcation areas affected by periodontal disease. Furcation involvement (FI) most commonly affects the mandibular molars. Diagnosis of furcation-involved teeth is mainly by the assessment of probing pocket depth, clinical attachment level, furcation entrance probing, and intraoral periapical radiographs. Three-dimensional imaging has provided advantage to the clinician in assessment of bone morphology. Thus, the present study aimed to compare the diagnostic efficacy of cone-beam computed tomography (CBCT) as against direct intrasurgical measurements of furcation defects in mandibular molars. Subjects and Methods: Study population included 14 patients with 25 mandibular molar furcation sites. CBCT was performed to measure height, width, and depth of furcation defects of mandibular molars with Grade II and Grade III FI. Intrasurgical measurements of the FI were assessed during periodontal flap surgery in indicated teeth which were compared with CBCT measurements. Statistical analysis was done using paired t-test and Bland–Altman plot. Results: The CBCT versus intrasurgical furcation measurements were 2.18 ± 0.86 mm and 2.30 ± 0.89 mm for furcation height, 1.87 ± 0.52 mm and 1.84 ± 0.49 mm for furcation width, and 3.81 ± 1.37 mm and 4.05 ± 1.49 mm for furcation depth, respectively. Results showed that there was no statistical significance between the measured parameters, indicating that the two methods were statistically similar. Conclusion: Accuracy of assessment of mandibular molar FI by CBCT was comparable to that of direct surgical measurements. These findings indicate that CBCT is an excellent adjunctive diagnostic tool in periodontal treatment planning.